The Effect Of Using Tiktok Videos Toward Students’ English Vocabulary Mastery At Smp Islam Abhariyah Jerneng, Lombok Barat - salisa maulida azmi (Sinar Lima, 2024)
TikTok is a social media platform that allows users to create videos accompanied by a wide selection of features such as music, filter stickers, and several other creative features. This study aims to determine the effect of using TikTok videos on the mastery of English vocabulary of 8th-grade students of SMP Islam Abhariyah Jerneng Lombok Barat. This research is a type of pre-experimental research with a post-test-only control Group Design. The population in the study were all 8th-grade students’, totaling 86 students of SMP Islam Abhariyah. The sampling technique used purposive sampling technique, namely class VIII C which amounted to 30 students, who were taken as samples in this study. The data collection technique used was a student pretest and posttest question sheet consisting of 20 questions. The data analysis technique in this study used the Paired Sample T-test. Based on the results of hypothesis testing that has been carried out, it can be concluded that the use of TikTok videos can bring effect toward students’ English vocabulary mastery of 8th-grade students at SMP Islam Abhariyah. This can be seen from the results of the significance value analyzed using the SPSS.22 application obtained a significance value of 0.000 where 0.000 < the probability value (P-Value) which is 0.05 so it can be concluded that (Ha ) is accepted and (Ho ) is rejected.